THE ROLES AND REWARDS FOR HEALTH VOLUNTEERS IN TUBERCULOSIS PROGRAM - Ratih Oktarinai; Dumilah Ayuningtyas (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: Abundance studies revealed the significant contribution of health volunteers or lay health workers in supporting health program, including for Tuberculosis program. This article aims to describe the cascade of volunteer involvement in community-based TB programs and to map out forms of rewards for volunteers. Methods: The searching was done from Pubmed, Scopus, Science Direct and Google Scholar. The three authors performed all steps of review started from searching, screening, and selecting the and conducted consensus to determine articles that are relevant and worthy of further analysis. We analyzed the manuscript with steps including generating the findings, coding the subthemes and doing thematic analysis. Result: As many as 13 studies were selected, of which were published after 2014. Most of the literature indicates that training (including transportation and meal costs) serves as both a reward and a means of sustaining volunteer efforts. Some studies also describe non-material rewards, such as recognition from health service providers, special access to health services, and symbolic items like uniforms or pins. Only a few studies mention specific amounts of material incentives. Nevertheless, this study supports the view that providing material rewards helps sustain field programs and enhances the commitment of health volunteers to TB prevention and control efforts at the community level.